1979
DOI: 10.1520/jte11219j
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive Bond Strength Prediction for Adhesive Joints

Abstract: An analytical study was carried out to derive the acoustic spectral response of an attenuating bond line. A similar effort was done to relate the time-base response of an attenuating bond line to the material properties of the adhesive. In this study, resonance separation, ultrasonic amplitude ratio, and resonance depth were related to the acoustic impedance, attenuation, and sound velocity of the adhesive layer. Experimental verification of the derived correlations was provided by systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Consequently, the signal treatment in this work is focused on the amplitude variations of the propagating SH wave. Experimentally, Flynn [16] and C. Gauthier et al [17][18][19] showed that the attenuation coefficient of guided waves in the medium were indeed related to the bonding strength and stiffness of the adhesives. In the field of nondestructive evaluation by SH type guided waves, mostly modes SH0, SH1 and rarely SH2 or SH3 have been exploited [20][21][22][23], aiming to identify defects of cohesive or adhesive nature or to detect the adhesive layer thickness [23].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the signal treatment in this work is focused on the amplitude variations of the propagating SH wave. Experimentally, Flynn [16] and C. Gauthier et al [17][18][19] showed that the attenuation coefficient of guided waves in the medium were indeed related to the bonding strength and stiffness of the adhesives. In the field of nondestructive evaluation by SH type guided waves, mostly modes SH0, SH1 and rarely SH2 or SH3 have been exploited [20][21][22][23], aiming to identify defects of cohesive or adhesive nature or to detect the adhesive layer thickness [23].…”
Section: Introductionmentioning
confidence: 99%